English Textbook for Class Five: An Analysis - Bhandari, Harishchandra (Journal of NELTA Gandaki, 2019)
This article explores the use of the global trends of English language teaching (ELT) found in the book 'School of English- Five'. As this article is an instance of document analysis, it reviews and assesses how much the global trends of ELT have been maintained in the contents of this primary level grade five's English reading material. While reviewing the recent trends along with the changes in perspectives, it is found that the author of the book has included the contents with wide coverage and sufficient amount of examples from various cultures with the intent of promoting multi-cultural awareness and intercultural communicative competence with a slight sense of world Englishes especially Nenglish to the early age of learners with sufficient examples of child friendliness and reflective practices. And it concludes that the application of this book helps to achieve the general objectives of teaching primary level English courses on the part of learners and suggests for including further recent and global trends that are gapped in the book.